2015
DOI: 10.3389/fncir.2015.00067
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-specific alternations in the amplitude of low-frequency fluctuations in chronic tinnitus

Abstract: Tinnitus, a phantom ringing, buzzing, or hissing sensation with potentially debilitating consequences, is thought to arise from aberrant spontaneous neural activity at one or more sites within the central nervous system; however, the location and specific features of these oscillations are poorly understood with respect to specific tinnitus features. Recent resting-state functional magnetic resonance imaging (fMRI) studies suggest that aberrant fluctuations in spontaneous low-frequency oscillations (LFO) of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 85 publications
(136 reference statements)
4
52
0
Order By: Relevance
“…Rauschecker et al (2010) developed a model to demonstrate structural and functional differences in ventromedial prefrontal cortex that were associated with tinnitus subjective loudness, indicating that frontal cortex may contribute to certain perceptual features of tinnitus. Resting-state fMRI studies have pointed out that the abnormalities of the frontal cortex could act as a direct mechanism of tinnitus chronification (Burton et al, 2012; Schmidt et al, 2013; Chen et al, 2014, 2015c,d, 2016), which are confirmed by the current meta-analysis. Based on the previous fMRI studies, the SFG has been regarded as a major integrative hub of the tinnitus network architecture (Chen et al, 2016), which can receive and integrate all kinds of information from different parts of the brain from inside and outside the body.…”
Section: Discussionsupporting
confidence: 83%
“…Rauschecker et al (2010) developed a model to demonstrate structural and functional differences in ventromedial prefrontal cortex that were associated with tinnitus subjective loudness, indicating that frontal cortex may contribute to certain perceptual features of tinnitus. Resting-state fMRI studies have pointed out that the abnormalities of the frontal cortex could act as a direct mechanism of tinnitus chronification (Burton et al, 2012; Schmidt et al, 2013; Chen et al, 2014, 2015c,d, 2016), which are confirmed by the current meta-analysis. Based on the previous fMRI studies, the SFG has been regarded as a major integrative hub of the tinnitus network architecture (Chen et al, 2016), which can receive and integrate all kinds of information from different parts of the brain from inside and outside the body.…”
Section: Discussionsupporting
confidence: 83%
“…fALFF has been applied as a proxy measure of spontaneous neural activity strength and has been used increasingly as a biomarker of neuropsychiatric diseases, including Alzheimer's disease (Zhou et al, 2015), schizophrenia (Xu et al, 2015), and depression (Liu et al, 2016). Several studies reported significant correlations of fALFF values and symptom severity in patients (Chen et al, 2015;Fryer et al, 2015) as well as behavioral performance in healthy humans (van Dam et al, 2015), suggesting a close association between resting-state fALFFs and specific behavioral parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Various functional magnetic resonance imaging (fMRI), electroencephalography, and magnetoencephalography (MEG) studies focusing on cerebral restingstate activity in targeted networks have shown alterations in functional connectivity or activity in different brain regions, including the auditory cortex (Burton et al, 2012;Kim et al, 2012;Maudoux et al, 2012a;Zhang et al, 2015), the prefrontal cortex (Kim et al, 2012, Maudoux et al, 2012a, 2012b, and the insula (Burton et al, 2012;Chen et al, 2015a;Vanneste, van de Heyning, & De Ridder, 2011) in tinnitus patients. Schmidt, Akrofi, Carpenter-Thompson, and Husain (2013) and Schmidt, Carpenter-Thompson, and Husain (2017) also observed a decreased functional connectivity in certain parts of the default mode network, particularly the prefrontal cortex and the cingulate posterior cortex with the precuneus.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, decreased ReHo values have been reported in the cuneus (Chen et al, 2015b) and the anterior lobe of the cerebellum (Yang et al, 2014) in subjects with tinnitus. This has led to the conclusion that chronic tinnitus induces changes in many cerebral networks, including the attention network (Chen et al, 2015b), the default mode network (Chen et al, 2015a), and the basal ganglia and the auditory cortex (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%